Mechanical properties and microstructure of cocos nucifera (coconut) coir fibres - Awang, Lokman; Salleh, Zulzamri; Mohd Yusop, Mohd Yuzri; Roslee, Ahmad Azmeer; Salit, Mohd Sapuan; Ishak, Mohamad Ridzwan (2012)
In this research, the mechanical properties of three types of coconut (cocos nucifera) fibres were investigated specifically young coconut (YC), ripe coconut (RP) and Komeng coconut (KC). Tensile test was carried out using Universal Testing Machine with a load capacity of 5kN in accordance to ASTM D 3379 standard for single fibre tensile test. Tensile test showed that tensile strength ranges between (0.10-31.15MPa) for KC, followed by RC(0.03-16.95MPa) and YC (0.07-12.01MPa). The morphology of these three coir fibres and shell surface were also investigated using optical microscope.